Pulmonary toxicity of inhaled nano-sized cerium oxide aerosols in Sprague–Dawley rats. Issue 6 (3rd July 2019) - Guo, Chang; Robertson, Sarah; Weber, Ralf J. M.; Buckley, Alison; Warren, James; Hodgson, Alan; Rappoport, Joshua Z.; Ignatyev, Konstantin; Meldrum, Kirsty; Römer, Isabella; Macchiarulo, Sameirah; Chipman, James Kevin; et al.
Abstract: Cerium oxide nanoparticles (CeO2 NPs), used in some diesel fuel additives to improve fuel combustion efficiency and exhaust filter operation, have been detected in ambient air and concerns have been raised about their potential human health impact. The majority of CeO2 NP inhalation studies undertaken to date have used aerosol particles of larger sizes than the evidence suggests are emitted from vehicles using such fuel additives. Hence, the objective of this study was to investigate the effects of inhaled CeO2 NP aerosols of a more environmentally relevant size, utilizing a combination of methods, including untargeted multi-omics to enable the broadest possible survey of molecular responses and synchrotron X-ray spectroscopy to investigate cerium speciation. Male Sprague–Dawley rats were exposed by nose-only inhalation to aerosolized CeO2 NPs (mass concentration 1.8 mg/m 3, aerosol count median diameter 40 nm) for 3 h/d for 4 d/week, for 1 or 2 weeks and sacrificed at 3 and 7 d post-exposure. Markers of inflammation changed significantly in a dose- and time-dependent manner, which, combined with results from lung histopathology and gene expression analyses suggest an inflammatory response greater than that seen in studies using micron-sized ceria aerosols. Lipidomics of lung tissue revealed changes to minor lipid species, implying specific rather than general cellular effects. Cerium speciation analysis indicated a change in Ce 3+ /Ce 4+ ratio within lung tissue. Collectively, these results in conjunction with earlier studies emphasize the importance of aerosol particle size on toxicity determination. Furthermore, the limited effect resolution within 7 d suggested the possibility of longer-term effects.